ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ALIH LAHAN KARET MENJADI PERKEBUNAN KELAPA SAWIT DI DESA PANDU RAYA KECAMATAN PARINDU KABUPATEN SANGGAU - Hengki Hengki; Dewi Kurniati; Shenny Oktoriana (Universitas Galuh Ciamis, 2021)
Indonesia support the development of oil palm cultivation, because nowadays oil palm is one important farm result, and then because oil palm plantation has the important aspect in social economic people life beside to give foreign exchange, and have many function and excellence thing of oil palm plantation and then see the condition that plantation sub sector have role or important effect such as social economic development that is give job field, give more income to the people that work in the plantation environment nor people around especially work in the oil palm plantation. The creation and expansion for the job field always have effort, especially by improvement of the development Rubber plant easy to try, but the management of rubber plantation often get the problem. Compared to rubber plant cultivation nowadaysoil palm more get interest from the farmer, while this plant can give advantage and give more income to the farmer. In the other hand, this research has purpose to know the factors that effects the farmer over of the rubber land become oil palm plantation in Parindu Raya village ParinduSanggau district. The population and sample in this study amounted of 40 farmers. Data were collected through a research questionnaire and direct interviews. The research method used is descriptive using ordinary last square (multiple linear regression) analysis. The results showed that age have positive and significant effect to over of the land. Experience, burden and price of oil palm has negative and significant effect to over of the land. Education, work time and fertilizer amount has negative and not significant effect to over of the land. Whereas, income deviation has positive and not significant effect to over of the land.